(untitled) (Research, Society and Development, 2021)
Objective: To analyze blood glucose levels generated by the portable glucometer, and to compare them with the levels given by the gold standard method. Methods: Search conducted in journals indexed in the MEDLINE / PUBMED, LILACS and SCIELO databases. The inclusion criteria of the analyzed studies were articles from the last 15 years (2005-2020), alteration of the glycemic profile, evaluation of other glucometers, portable and table devices, venous and capillary blood glucose. Results: The study found that the validated devices were Accu-Chek Active (Roche Diagnóstica), Accu-Chek Advantage (Roche Diagnóstica), Contour TS (Bayer) compared respectively with standard laboratory methods, unspecified, Prietest Touch (Katal), Flexor EL200 in the adult and elderly population. In order to be approved and have validation confirmed, portable glucometers need to meet the standards of the International Organization for Standardization (ISO: 15197: 2003). Conclusion: Only 3 portable glucometers were validated when compared to the gold standard. Bearing in mind that the use of medications and the adequate control of dysglycemia is closely linked to the measurements generated by glucometers, the use of invalidated devices puts the health, treatment and quality of life of diabetic users at risk.